PERANCANGAN SISTEM INFORMASI RAPORT ONLINE BERBASIS WEB KURIKULUM 2013 (K-13) PADA SMK AL-ANHAR BAYANG - Sindi Pratama Putri; Jusmita Weriza (Jurnal Manajemen Teknologi Informatika, 2024)
The assessment sheets at vocational schools still use Microsoft Excel and Microsoft Word programs. After that, the assessment sheets will be filled in by teachers in the field of study and when filling out report cards is still very prone to errors, manual report cards can have varying or less consistent formats due to limited time, teachers are in a hurry. -haste in providing assessments and errors in writing or inputting data in making manual reports can affect the accuracy and consistency of information. The research method used is by analyzing the current system and identifying needs using the system development life cycle (SDLC) with UML design tools. This information system was created to make the process of creating report cards at Al-Anhar Bayang Vocational School easier and more effective and efficient because all data has been stored in database form and produces more accurate report card output as expected. The Online Report Card information system at Al-Anhar Bayang Vocational School has been computerized so that it can save time and energy compared to the old system and report cards are more effective and efficient